Impact of the herbal medicine, Ephedra sinica stapf, on gut microbiota and body weight in a diet-induced obesity model - Song, Eun-Ji; Shin, Na Rae; Jeon, Songhee; Nam, Young-Do; Kim, Hojun (Frontiers in Pharmacology, 2022)
Obesity is a chronic metabolic disease caused by excessive body fat and has become a global public health problem. Evidence suggests that obesity and obesity-induced metabolic disorders are closely related to gut microbiota. Bupropion (BP), an antidepressant medicine, and Ephedra sinica Stapf [Ephedraceae; Ephedrae Herba], a herbal medicine, are sympathetic stimulants and have weight loss effects. However, to our best knowledge, no studies have simultaneously assessed the effects of drugs and herbal medicines on obesity and gut microbiota. This study aimed to determine the effects of BP and ES on weight loss and re-modulation of host gut microbiota. To test this hypothesis, we fed C57BL/6J mice with a high-fat diet supplemented with bupropion (BP; 30 mg/kg/day) and Ephedra sinica Stapf extract (ES; 150 mg/kg/day) via oral gavage for eight weeks. Further, we evaluated the effects of BP and ES on body weight and fat accumulation. In addition, we evaluated the effects of BP and ES on gut microbiota using 16S rRNA amplicon sequencing. Our results showed that weight loss was confirmed in both BP and ES; however, it was more pronounced in ES. ES changed the overall composition of the gut microbiota by restoring the relative abundance of Oscillospiraceae, Lachnospiraceae, and the Firmicutes/Bacteroidetes ratio, an indicator of gut microbiota dysbiosis. Nine amplicon sequence variants (ASVs) of the gut microbiome were significantly recovered by BP and ES treatment, of which eight ASVs correlated with body weight and fat accumulation. Additionally, three ASVs were significantly recovered by ES treatment alone. In conclusion, the anti-obesity effects of BP and ES, especially fat accumulation, are related to the regulation of gut microbiota. Moreover, ES had a greater influence on the gut microbiota than BP.